DIGITAL BUSINESS COMPETENCIES AND HUMAN CAPABILITIES IN THE HOSPITALITY INDUSTRY: DRIVING EMPLOYEE ADAPTABILITY AND SERVICE EXCELLENCE - Widya Granita; Zairil (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
The rapid digital transformation in the hospitality industry has significantly reshaped service delivery processes, operational systems, and employee competency requirements. This study aims to examine the influence of Digital Business Competencies on Service Excellence, with Employee Adaptability acting as a mediating variable within the hospitality industry. Grounded in Dynamic Capability Theory, this study investigates how employees’ digital competencies contribute to organizational service performance in increasingly technology-driven hospitality environments. A quantitative research approach was employed using a cross-sectional survey design. Data were collected from 286 hospitality employees working in hotels, resorts, restaurants, and tourism-related service organizations that have implemented digital technologies in their operational activities. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The findings reveal that Digital Business Competencies significantly influence Employee Adaptability and Service Excellence. Furthermore, Employee Adaptability demonstrates a significant positive effect on Service Excellence and partially mediates the relationship between Digital Business Competencies and Service Excellence. The study highlights that digital transformation in hospitality should not focus solely on technological investment but must also emphasize human capability development and workforce adaptability. The findings contribute to the growing literature on human-centered digital transformation by integrating technological capability and employee adaptability into a unified hospitality service framework. Practically, the study provides important managerial implications for hospitality organizations in designing digital competency development programs, adaptive workforce strategies, and sustainable service excellence initiatives in digitally evolving hospitality environments.